Penyitaan Berbasis Properti Sebagai Upaya Pengembalian Kerugian Keuangan Negara Dalam Tindak Pidana Korupsi - Musfiratul Ilmi; Syamsuddin Muchtar; Amir Ilyas (Jurnal USM Law Review)
This study aims to analyze the application of property-based returns on state financial losses. The research method used is empirical by using primary and secondary data sources. Data was collected by interviewing a special criminal prosecutor and analyzing three court decisions. This study, not only discusses the return of state losses but also discusses solutions so that the execution of recovering state losses can be maximized. This research is based on the theory of economic analysis of law. This study resulted in three points, the first is that property-based confiscation are only used for proof. Second, as the basis for recovering state financial losses, the model used is value-based confiscation. Third, the return of state financial losses is still an option that can be replaced with a substitute imprisonment. Supposedly, corruption convicts should not be given a choice of alternative prisons but can be replaced with sanctions in the form of social work which can be calculated as the value of state losses. In addition, the draft asset return law must be ratified by referring to UNCAC 2003 so that there are rules governing the return of assets.